Glial origin of mesenchymal stem cells in a tooth model system - Kaukua, Nina; Shahidi, Maryam Khatibi; Konstantinidou, Chrysoula; Dyachuk, Vyacheslav; Kaucka, Marketa; Furlan, Alessandro; An, Zhengwen; Wang, Longlong; Hultman, Isabell; Ährlund-Richter, Lars; Blom, Hans; Brismar, Hjalmar; et al. (Nature (London), 2014)
In the mouse, nerve-associated peripheral glial cells give rise to mesenchymal stem cells that contribute to the development and growth of adult teeth. Glial cells as a source of multipotency This study of tooth organogenesis in the continuously growing mouse incisor system shows that nerve-associated peripheral glial cells can give rise to mesenchymal stem cells that contribute to the development and growth of adult teeth. Mesenchymal stem cells are being used as a source of adult stem cells in numerous clinical trials, and the existence of a glia-to-mesenchymal cell transition raises interesting questions about what other cell types may share a glial origin. Mesenchymal stem cells occupy niches in stromal tissues where they provide sources of cells for specialized mesenchymal derivatives during growth and repair 1 . The origins of mesenchymal stem cells have been the subject of considerable discussion, and current consensus holds that perivascular cells form mesenchymal stem cells in most tissues. The continuously growing mouse incisor tooth offers an excellent model to address the origin of mesenchymal stem cells. These stem cells dwell in a niche at the tooth apex where they produce a variety of differentiated derivatives. Cells constituting the tooth are mostly derived from two embryonic sources: neural crest ectomesenchyme and ectodermal epithelium 2 . It has been thought for decades that the dental mesenchymal stem cells 3 giving rise to pulp cells and odontoblasts derive from neural crest cells after their migration in the early head and formation of ectomesenchymal tissue 4 , 5 . Here we show that a significant population of mesenchymal stem cells during development, self-renewal and repair of a tooth are derived from peripheral nerve-associated glia. Glial cells generate multipotent mesenchymal stem cells that produce pulp cells and odontoblasts. By combining a clonal colour-coding technique 6 with tracing of peripheral glia, we provide new insights into the dynamics of tooth organogenesis and growth.